A long clinical course with late distant metastases from follicular thyroid carcinoma - Erok, Berrin; Harmancı, Kemal; Aksaray, Ferdi; Unlu, Nazmi Uğur; Aydın, Seckin (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Follicular thyroid carcinoma (FTC) accounts for 10-20% of the differentiated thyroid carcinomas (DTCs), and it is the second most common thyroid malignancy after papillary thyroid carcinoma (PTC). FTC is typically more common in women and in older age group than PTC. Unlike PTC, FTC metastases late to the lymph nodes, with only up to 10-20% of the patients having nodal metastases at the time of diagnosis.On the other hand, distant metastasis via hematogenous spread is more likely in patients with FTC due to the invasion of blood vessels. Prognosis depends on the extent of the distant metastasis which drop 10-year survival significantly. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Although DTCs have usually favorable prognosis, metastatic disease in these patients has a long clinical course. Cranial imaging in these patients should be performed during the follow-up after the treatment of FTC with thyroidectomy and RAI. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. We report a case of late onset but catastrophic hematogenous distant metastases beginning 8 years after the diagnosis & treatment of FTC and becommimg widespread during the following 10 years with a long clinical course in a 60 year old female patient. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In the RAI refractory metastatic lesions SRS and surgical resections should be conserned as the first management approach to improve survival.